Electrical characteristics and photosensing properties of Al/symmetrical CuPc/p-Si photodiodes - Demirezen, S.; Al-Sehemi, A. G.; Yuzer, A.; Ince, M.; Dere, A.; Al-Ghamdi, A. A.; Yakuphanoğlu, Fahrettin (Springer, 2022)
In this study, the symmetrical copper-phthalocyanine (CuPc) was coated on p-Si wafer by spin-coating method. The photoresponse and electrical properties of the Al/symmetrical CuPc/p-Si structures/diodes were investigated at room temperature using by current-voltage/time (I-V/t) and capacitance/conductance-voltage/frequency (C/G-V/f) measurements under dark and various solar irradiances (between 10 and 100 mW/cm(2)). The main electronic parameters of the diode, which included ideality factor (n), barrier height (phi(b)), rectification ratio (RR = I-F/I-R), series resistance (R-s), and interface states density (N-ss) were computed. The experimental results reveal that the photocurrent level of the diodes is controlled by various solar irradiances. The m exponent of the double-logarithmic I-ph-P plot was found to be 1.12, confirming linear photoconduction behavior. The Al/symmetrical CuPc/p-Si structure can be used as a photo device/sensor in electro-optic and photonics.
Keywords: Voltage Characteristics; Capacitance-Voltage; Temperature; Dependence